General Rojas Pinilla’s political trial in the Congress of republic of Colombia (1958-1959) and the conspiracy against the “Frente Nacional”. - Valencia Gutiérrez, Alberto (Sociedad y Economía, 2010)
This article offers an overview of the characteristics of political trial that follows the general Gustavo Rojas Pinilla, ex-President of Colombia (1953-1957), in the Congress of the Republic, during the period from August 18, 1958 and April 2, 1959. Presents, in addition, the characteristics of the political framework in which develops the trial that is carried out at the time to be put into operation the political pact of the National Front and builds a threat of conspiracy against the same pact around the return of General to the country after his departure of the government. The article closes with a series of findings related to the effects of the trial and the construction of the collective memory of this time.